Design and development of a data acquisition and monitoring system - Su, Myat Nandar. (2013)
Nowadays, as people are getting interested in knowing the energy usages of their home appliances, reliable, accurate and inexpensive real-time power monitoring devices are in high demand and will be useful for every household. In real time power measurement, every instance of current and voltage of devices can be monitored and then the power consumption of each appliances are easily estimated which will help customers for avoiding energy wastes and optimum usage of electrical supply.